Mathematical modelling of unsteady free convection boundary layer flow over a three-dimensional stagnation point - Admon, Mohd. Ariff (2011)
The three-dimensional axisymmetric stagnation point flow have applications in many manufacturing processes in industry such as the boundary layer along material handling conveyers, the aerodynamic extrusion of plastic sheet, and the cooling of an infinite metallic plate in cooling bath. In this thesis, mathematical models to study the heat and mass transfer of an unsteady three-dimensional body near the stagnation point are developed. Problems considered involve the flow in viscous fluid and micropolar fluid. In addition, the effect of heat generation is also considered for viscous fluid problem. The governing equations which consist of coupled nonlinear partial differential equations are solved numerically through an implicit finite difference scheme known as the Keller-box method. The results presented include the velocity, temperature and microrotation profiles as well as the fluid flow and heat transfer characteristics for various parametric physical conditions such as the absorption parameter, Q and the material or micropolar parameter, K. The results obtained show that the effect of heat generation, Q gives rises to the skin friction and heat transfer coefficients. However, the skin friction and heat transfer coefficients are decreased when the material parameter, K is increased.